2018
DOI: 10.1089/end.2017.0915
|View full text |Cite
|
Sign up to set email alerts
|

Thulium Laser Treatment of Upper Urinary Tract Carcinoma: A Multi-Institutional Analysis of Surgical and Oncological Outcomes

Abstract: TL management of UTUC is a safe and efficacious conservative treatment. Our experience shows optimal vaporization and hemostatic control in the absence of major complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 25 publications
3
41
0
1
Order By: Relevance
“…The conclusions of the authors are also supported by a recent series of 42 patients treated endoscopically with Tm:YAG laser for both low‐risk and high‐risk UTUC; optimal vaporization and hemostasis was obtained in the absence of major complications, and just 12% of the patients required a second‐look procedure, 19% of the patients experienced clinical recurrence, 9.5% of the patients required radical nephroureterectomy and no progression or upstaging of disease occurred after a median follow‐up period of 26 months.…”
mentioning
confidence: 63%
“…The conclusions of the authors are also supported by a recent series of 42 patients treated endoscopically with Tm:YAG laser for both low‐risk and high‐risk UTUC; optimal vaporization and hemostasis was obtained in the absence of major complications, and just 12% of the patients required a second‐look procedure, 19% of the patients experienced clinical recurrence, 9.5% of the patients required radical nephroureterectomy and no progression or upstaging of disease occurred after a median follow‐up period of 26 months.…”
mentioning
confidence: 63%
“…No patients discontinued therapy due to AEs. In the report by Musi and colleagues, Grade 1, 2, and 3 AEs were reported in 38%, 47.6%, and 2.4%, respectively [9]. An important consideration is that we cannot definitively identify topical therapy directly caused these local adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic management of UTUC via a percutaneous or ureteroscopic approach is feasible and safe in selected patients[4]. Unfortunately, reported recurrence rates following this treatment modality range from 30% to 70% depending upon tumor stage and grade[6,8], although a recent study by Musi and colleagues using the Thulium laser has shown lower recurrence rates of 20–25% after a median follow up of 26.3 months [9]. In bladder cancer, intravesical instillation therapy has been established as a viable adjuvant therapy to reduce recurrence and progression of superficial disease[10].…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis examining the impact of URS before RNU on oncological outcomes [15], patients with initial URS had a significantly higher risk of bladder recurrence; however, that had no impact on CSS, OS, recurrence-free survival (RFS), or metastasis-free survival (MFS). Several options are available for laser ablation, such as holmium, thulium, and neodymium, but there is little evidence regarding the pros and cons of the different modalities [16].…”
Section: Treatment Selectionmentioning
confidence: 99%